Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/rs10060958
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Environmental Loading Corrections on the Nonlinear Variations and Velocity Uncertainties for the Reprocessed Global Positioning System Height Time Series of the Crustal Movement Observation Network of China

Abstract: Mass redistribution of the atmosphere, oceans, and terrestrial water storage generates crustal displacements which can be predicted by environmental loading models and observed by the Global Positioning System (GPS). In this paper, daily height time series of 235 GPS stations derived from a homogeneously reprocessed Crustal Movement Observation Network of China (CMONOC) and corresponding loading displacements predicted by the Deutsche GeoForschungsZentrum (GFZ) are compared to assess the effects of loading cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Moreover, unmodeled nonstationary signals will also have an effect on velocities and their uncertainties [35,52]. Filtering unmodeled CMCs will not only improve the precision of the velocity due to the interannual elastic loading correction, but also improve the signal-to-noise ratio of the velocity [16,53]. Therefore, the CMCs in GPS time series should be considered when estimating the ground velocity using regionally dense GPS sites.…”
Section: Velocities and Uncertainties Of The Etpmentioning
confidence: 99%
“…Moreover, unmodeled nonstationary signals will also have an effect on velocities and their uncertainties [35,52]. Filtering unmodeled CMCs will not only improve the precision of the velocity due to the interannual elastic loading correction, but also improve the signal-to-noise ratio of the velocity [16,53]. Therefore, the CMCs in GPS time series should be considered when estimating the ground velocity using regionally dense GPS sites.…”
Section: Velocities and Uncertainties Of The Etpmentioning
confidence: 99%
“…The nonlinear variations of GPS coordinate time series contain a variety of geophysical signals. Current research focuses are on the displacements of GPS stations under the impact of surface environmental loadings such as atmospheric pressure, oceanic tide and hydrology [19,39]. The displacements caused by environmental loadings in vertical component (Up) are much bigger than that in horizontal components (North and East).…”
Section: Relevant Geophysical Signalsmentioning
confidence: 99%
“…Effective extraction of CMC is quite beneficial in improving the accuracy of coordinate time series, quantifying the station displacement caused by geophysical signals and accurately describing the features of regional earth surface deformation. As a result, recent years have seen CMC become a heated research topic [9][10][11][12][13][14][15][16][17][18][19]. Jiang et al [20] analyzed 29 stations in the Chinese CORS network and extracted the CMC series by using a PCA method.…”
Section: Introductionmentioning
confidence: 99%
“…In recent two decades, many researchers have undertaken various topics on earth science by means of Global Positioning System (GPS) time series obtained from continuous GPS (CGPS) stations, including analysis of periodic signals [1][2][3][4][5], detection of stochastic models [6][7][8][9], spatial filtering methods [10][11][12][13][14], and surface loading models (SLMs) [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two years, the effect of ELCs is still a heated topic. Yuan et al [22] analyzed 235 Crustal Movement Observation Network of China (CMONOC) stations for the nonlinear motion at GPS stations. They calculated the displacement series caused by environmental loadings (including atmospheric loading, nontidal oceanic loading and hydrological loading) and found that after ELCs, the average root mean square (RMS) of GPS height time series could be reduced by~20%.…”
Section: Introductionmentioning
confidence: 99%